Deploying Orientalism in culture and history from Germany to Central and Eastern Europe - Hodkinson, James 1973-; Walker, John 1956-; Mazumdar, Shaswati; Feichtinger, Johannes 1967- (Boydell & Brewer, 2013)
The concept and study of orientalism in Western culture gained a changed understanding from Edward Said's now iconic 1978 book Orientalism. Especially in Germany, however, recent debate has moved beyond Said's definition ofthe phenomenon, highlighting the multiple forms of orientalism within the "West," the manifold presence of the "East" in the Western world, indeed the epistemological fragility of the ideas of "Occident" and "Orient" as such.This volume focuses on the deployment -- here the cultural, philosophical, political, and scholarly uses -- of "orientalism" in the German-speaking and Central and Eastern European worlds from the late eighteenth century to thepresent day. Its interdisciplinary approach combines distinguished contributions by Indian scholars, who approach the topic of orientalism through the prism of German studies as practiced in Asia, with representative chapters by senior German, Austrian, and English-speaking scholars working at the intersection of German and oriental studies. Contributors: Anil Bhatti, Michael Dusche, Johannes Feichtinger, Johann Heiss, James Hodkinson, Kerstin Jobst, Jon Keune, Todd Kontje, Margit Köves, Sarah Lemmen, Shaswati Mazumdar, Jyoti Sabarwal, Ulrike Stamm, John Walker. James Hodkinson is Associate Professor in German Studies at Warwick University. John Walker is Senior Lecturer in European Cultures and Languages at Birkbeck College, University of London. Shaswati Mazumdar is Professor in German at the University of Delhi. Johannes Feichtinger is a Researcher at the österreichische Akademie der Wissenschaften
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte; Orientalism / Germany / History; Orientalism / Europe, Central / History; Orientalism / Europe, Eastern / History; Travelers' writings, European / History and criticism; Orientalism in literature; Orientalismus -- Kunst; Deutschland; Europa; Europe / Civilization / Oriental influences; Orient / In literature; Mitteleuropa; Aufsatzsammlung